Nebulous: A Framework for Scientific Applications Execution on Cloud Environments - Galante, Guilherme; Bona, Luis Carlos E. de (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2011)
This paper presents a framework, called Nebulous, designed to simplify the execution of MPI and OpenMP parallel applications in computational clouds. The framework aims to automate the process of deployment and execution, avoiding the direct user interaction with the cloud. The framework is built on a cloud middleware layer (e.g. OpenNebula, Eucalyptus or Nimbus) and consists of three components: the Resource Description Block, an Application Programming Interface and the Executor. According to the results, Nebulous allows users to deploy applications over varying numbers of nodes in a simple way, uniformly, scalably and with minimum effort.